The Influence of Work-Life Balance and Work Environment on Employee Job Satisfaction: Case Study at SEA Today Company - Indriyani, Yulia; Adhi, Triyogo Moelyo (CV ODIS, 2024)
Employees are a very important part of the company's sustainability. In maintaining employee performance so that it remains productive, it is necessary to pay attention to employee job satisfaction. An employee's job satisfaction in an organization cannot be separated from the work environment and work-life balance. This research aims to determine the influence of Work-Life Balance and Work Environment on Employee Job Satisfaction (Case Study at SEA Today Company). The method used in this research is a survey method with a quantitative approach. The sampling technique used was saturated sampling. Research data processing uses the SPSS version 27 application. The population of this study was all 57 employees of SEA Today's operational division. The results of this research show that work-life balance and the work environment have a positive and significant effect on job satisfaction, with a significant difference in the r-value of 5% and a higher Cronbach's Alpha value. These results show that improving work-life balance and the work environment can increase employee job satisfaction. The results of the hypothesis simultaneously conclude that work-life balance and the work environment have a positive and significant effect on employee job satisfaction at the SEA Today company.